King, priest, prophet positive eschatological protagonists of the Qumran library - Xeravits, Géza G. 1971-2019 (2002)
Nederlands samenvatting
Literaturverz. S. [229] - 248
Groningen, Rĳksuniv., Proefschr., 2002
Archivierung prüfen
Keywords: Dead Sea Scrolls; Eschatology, Jewish; Messiah -- Judaism; Hochschulschrift